Uniqcall Education Learning Service Management Model to Improve Students' Self-Esteem at Madrasah Aliyah Al-Fatah Cikembang, Kertasari District, Bandung Regency - Luthfi Audia Pribadi; Dedy Achmad Kurniady; Suryadi Suryadi; Nugraha Suharto; Zhang Shuhua (Jurnal Mamangan, 2026)
This study addresses the problem of low self-esteem among students in rural madrasah, which is primarily caused by uniform instructional practices and limited attention to learners’ psychological needs. Such conditions contribute to poor self-confidence, low motivation, and weak learning engagement. The purpose of this research is to develop and examine the effectiveness of the Uniqcall Education Learning Service Management Model in improving students’ self-esteem at Madrasah Aliyah Al-Fatah Cikembang, Kertasari District, Bandung Regency. The study is theoretically based on Self-Determination Theory, Self-Efficacy Theory, and Universal Design for Learning, which emphasize autonomy, competence, relatedness, and inclusive instructional design as foundations for positive student development. The research employed a Research and Development approach using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through observation, interviews, documentation, and a standardized self-esteem questionnaire administered before and after the intervention. Quantitative analysis demonstrated a statistically significant increase in students’ self-esteem after the implementation of the Uniqcall Education model. The findings show strengthened dimensions of autonomy, competence, and social relatedness, supported by more personalized, collaborative, and technology-assisted learning services. The model successfully created meaningful learning experiences and improved student psychological well-being. This study concludes that the Uniqcall Education learning service management model is effective in enhancing self-esteem and supporting student development in madrasah contexts. The novelty lies in an integrated management model that combines psychological development principles with learner-centered services, positioning self-esteem improvement as a central outcome of educational management and offering a replicable framework for school quality improvement.